Mann's pharmacovigilance - Andrews, Elizabeth B.; Moore, Nicholas (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley Blackwell, 2014)
Mann's Pharmacovigilance is the definitive reference for the science of detection, assessment, understanding and prevention of the adverse effects of medicines, including vaccines and biologics. Pharmacovigilance is increasingly important in improving drug safety for patients and reducing risk within the practice of pharmaceutical medicine. This new third edition covers the regulatory basis and the practice of pharmacovigilance and spontaneous adverse event reporting throughout the world.
ICH-E2C Topic: Clinical Safety Data Management -- Periodic Benefit-Risk Evaluation Report (PBRER).
Preceded by Pharmacovigilance / editors, Ronald D. Mann, Elizabeth B. Andrews. 2nd ed. c2007.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Pharmacovigilance; Drug-Related Side Effects and Adverse Reactions -- classification; Internationality; Pharmacoepidemiology -- Methods; Product Surveillance, Postmarketing; Pharmacovigilance; Drug-Related Side Effects and Adverse Reactions -- classification; Internationality; Pharmacoepidemiology -- methods; Product Surveillance, Postmarketing; Drug-Related Side Effects and Adverse Reactions -- classification; Internationality; Pharmacoepidemiology -- methods; Pharmacovigilance; Product Surveillance, Postmarketing; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Pharmacoepidemiology; Electronic books; Electronic books